The newsroom. The complete second season [videorecording (DVD)] - Daniels, Jeff, 1955-; Mortimer, Emily; Waterston, Sam (Home Box Office : Warner Home Video, 2014)
The Newsroom takes a behind-the-scenes look at a high-rated cable-news program at the fictional ACN Network, focusing on the on and off camera lives of its acerbic anchor, a new executive producer, and their newsroom staff.